Land‐use type and intensity differentially filter traits in above‐ and below‐ground arthropod communities. (28th February 2017) - Birkhofer, Klaus; Gossner, Martin M.; Diekötter, Tim; Drees, Claudia; Ferlian, Olga; Maraun, Mark; Scheu, Stefan; Weisser, Wolfgang W.; Wolters, Volkmar; Wurst, Susanne; Zaitsev, Andrey S.; Smith, Henrik G.
Summary: Along with the global decline of species richness goes a loss of ecological traits. Associated biotic homogenization of animal communities and narrowing of trait diversity threaten ecosystem functioning and human well‐being. High management intensity is regarded as an important ecological filter, eliminating species that lack suitable adaptations. Below‐ground arthropods are assumed to be less sensitive to such effects than above‐ground arthropods. Here, we compared the impact of management intensity between (grassland vs. forest) and within land‐use types (local management intensity) on the trait diversity and composition in below‐ and above‐ground arthropod communities. We used data on 722 arthropod species living above‐ground (Auchenorrhyncha and Heteroptera), primarily in soil (Chilopoda and Oribatida) or at the interface (Araneae and Carabidae). Our results show that trait diversity of arthropod communities is not primarily reduced by intense local land use, but is rather affected by differences between land‐use types. Communities of Auchenorrhyncha and Chilopoda had significantly lower trait diversity in grassland habitats as compared to forests. Carabidae showed the opposite pattern with higher trait diversity in grasslands. Grasslands had a lower proportion of large Auchenorrhyncha and Carabidae individuals, whereas Chilopoda and Heteroptera individuals were larger in grasslands. Body size decreased with land‐use intensity across taxa, but only in grasslands. The proportion of individuals with low mobility declined with land‐use intensity in Araneae and Auchenorrhyncha, but increased in Chilopoda and grassland Heteroptera. The proportion of carnivorous individuals increased with land‐use intensity in Heteroptera in forests and in Oribatida and Carabidae in grasslands. Our results suggest that gradients in management intensity across land‐use types will not generally reduce trait diversity in multiple taxa, but will exert strong trait filtering within individual taxa. The observed patterns for trait filtering in individual taxa are not related to major classifications into above‐ and below‐ground species. Instead, ecologically different taxa resembled each other in their trait diversity and compositional responses to land‐use differences. These previously undescribed patterns offer an opportunity to develop management strategies for the conservation of trait diversity across taxonomic groups in permanent grassland and forest habitats. Abstract : The strong effects of land‐use type and intensity on trait composition suggest that conversion of forest to grassland and management intensification within land‐use types will lead to filtering of traits in several above‐ and below‐ground arthropod taxa. These losses of traits are not predictable based on simple classifications into above‐ or below‐ground arthropod taxa.